Breed-Specific Variations in Blood Metabolites and Cortisol Reduction in Response to Organic Mineral Supplementation in Simmental and Holstein Calves - C. Uyarlar; A. Rahman; E. E. Gültepe; İ. S. Çetingül; Ü. Özçınar; M. U. Akhtar; İ. Bayram (Tropical Animal Science Journal, 2026)
Early life immunity and stress regulation are critical for the health and survival of newborn calves. Trace minerals like selenium, zinc, and chromium, especially when obtained from organic sources, play an important role in immune and defense systems and in stress physiology. This study examined the effects of supplementing Holstein and Simmental calves with a blend of organic minerals (chromium, selenium, and zinc) on immune and stress responses and blood metabolites. Twenty Holstein and 20 Simmental calves were divided into four groups in a 2 × 2 factorial arrangement, with breed as the first and organic mineral supplementation as the second factor. In addition to milk, each calf received a mixture of organic selenium, chromium, and organic zinc (0.5 g each) orally for 21 days after birth. Calves in the control group did not receive any organic mineral supplement. Blood samples were collected from the jugular vein of all calves seven times: on the day of birth, after 3 days, and then once per week until weaning after the completion of oral mineral supplementation. Serum alanine transaminase, aspartate transaminase, gamma glutamyl transferase, high-density lipoprotein, low-density lipoprotein, and total cholesterol concentrations were 27%, 19.1%, 21.2%, 15.5%, 12.5%, and 13% higher, respectively, in Simmental calves than in Holstein calves, during the first week after birth. The addition of an organic mineral mixture to drinking milk did not affect blood metabolites in either breed (p>0.05), except for a 35% decrease in serum cortisol levels in both breeds during week 3 (p<0.021). Overall, it was concluded that organic minerals, in addition to milk, may have protective potential against stress by reducing serum cortisol levels during periods of stress in newborn calves of both Simmental and Holstein breeds.